1991
DOI: 10.1073/pnas.88.7.2658
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of the interleukin 1 receptor antagonist into an agonist by site-specific mutagenesis.

Abstract: Interleukin 1 (IL-1) receptor antagonist (IL-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 33 publications
1
40
1
Order By: Relevance
“…Due to the conservation of the ligand-binding domains of sIL-1RAcP, this molecule may still share the receptor complex stabilizing function, thereby acting as an inhibitor of IL-1 signaling through formation of an IL-1 trap. This action of sIL-1RAcP could therefore be distinct from IL-1Ra-mediated inhibition of IL-1 signaling, since binding of IL-1Ra to the IL-1RI does not lead to recruitment of IL-1RAcP (4,37,38). In this study, we compared the effect of both inhibitors on CIA.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the conservation of the ligand-binding domains of sIL-1RAcP, this molecule may still share the receptor complex stabilizing function, thereby acting as an inhibitor of IL-1 signaling through formation of an IL-1 trap. This action of sIL-1RAcP could therefore be distinct from IL-1Ra-mediated inhibition of IL-1 signaling, since binding of IL-1Ra to the IL-1RI does not lead to recruitment of IL-1RAcP (4,37,38). In this study, we compared the effect of both inhibitors on CIA.…”
Section: Discussionmentioning
confidence: 99%
“…2A). Changing it to lysine, as found in IL-1Ra (Lys 145 ), drastically reduces the agonistic activity of IL-1b, whereas the reverse mutation renders IL-1Ra partially agonistic (31,32). In the IL-1R complex structures, IL-1b residue Asp 145 makes a direct hydrogen bond to Ser 185 of IL-1RAcP (Supplemental Fig.…”
Section: Charge Effects On Binding To Il-1racp and Il-36r Signalingmentioning
confidence: 99%
“…In addition to the importance of the b4/5 and b11/12 loops, it has been reported that a charged residue directly C-terminal of the b11/12 loop has a large influence on the agonist and antagonistic properties of IL-1b relative to IL-1Ra (31). In IL-1b this residue is an aspartate (Asp 145 ) (Fig.…”
Section: Charge Effects On Binding To Il-1racp and Il-36r Signalingmentioning
confidence: 99%
“…The next step was to test the (51), in black and red, respectively). The asterisk indicates a residue, which together with the loop region between ␤4 and ␤5, is crucial in determining antagonist activity in IL-1ra (49,52). The amino acid coloring scheme depicts chemically similar residues: green (hydrophobic); red (acidic); blue (basic); yellow (C); orange (aromatic); black (structure breaking); and gray (tiny).…”
Section: Il-1␦ and Il-1⑀ Do Not Activate Nf-b Through Classical Il-1rsmentioning
confidence: 99%